Music interferes with expectation-induced pain modulation: a controlled cross-over experimental study - Mélysiane Marcotte; Pierre Rainville; Dan Tcaciuc; Anna Bendas; Todd A. Vogel; Robert Durand; Mathieu Roy; Elham Emami; Nathalie Gosselin (PAIN Reports)
Abstract. Introduction:. Music reduces pain and anxiety in various contexts, but the possible effect on pain anticipatory mechanisms remains unclear. Objectives:. This study examines the effects of a standardized musical intervention (Music Care) on pain perception and on pain modulation induced by expectations of low or high pain. Methods:. Healthy participants were tested in an experimental study using a crossover design involving the musical intervention counterbalanced with an active auditory control condition (audiobook) and a silent control condition. Pain perception was assessed using contact heat stimulation, and expectations were manipulated using prestimulus anticipatory cues signalling high or low pain. Results:. Perceived pain intensity, measured using a visual analog scale, was decreased during the music intervention and the audiobook compared to silence (P's < 0.001). Music was more effective than the audiobook control, especially at the higher pain stimulation level (P < 0.001). Anticipatory cues modulated pain and anxiety in the expected direction across all conditions (P's < 0.001). Music and the audiobook produced comparable reduction in (1) expectation-induced (1a) hypoalgesic and (1b) hyperalgesic effects (all P's < 0.005) and in (2) pain anticipatory anxiety (all P's < 0.05). Overall, music was more effective than the active auditory control to reduce pain but both forms of auditory distraction partly blocked the modulatory effects of low and high pain expectations. Conclusion:. This study highlights the multiplicity of processes contributing to music-induced analgesia and suggests that music may help improve pain management in the context of high pain expectation and anxiety. However, music may also interfere with pain-relieving strategies involving the induction of low pain expectations.